Implementation of 5s and kaızen methods for developing a novel wage assessment method in a steel construction factory: an application in Turkey - Önay, Mehmet Burçin; Seçkiner, Serap Ulusam (Universitas Ahmad Dahlan, 2024)
The study aims to implement the 5S (seiri, seiton, seiso, seiketsu, and shitsuke) method and KAIZEN for emphasizing the troubles and defective products, establishing work standards, implementing fair wage assessments based on job analysis and job evaluations in a steel construction factory. A more objective wage assessment method is developed, and workers' unrest can be resolved fairly. 5S and KAIZEN studies have been applied for two years in a steel construction factory. Then, the evaluation of success factors within the internal structure of wage brackets utilized last year's 5S scores to enhance employees' confidence in the objectiveness of the wage system assessment. A reformer method for assessing wages has been created and implemented, integrating lean manufacturing principles and a job analysis and evaluation system. The framework has been tested and implemented only for a steel construction factory. In the future, studies could be conducted to assess different sector factories. The proposed framework has been successfully implemented in a medium-large scale manufacturing factory. A novel wage assessment framework that involves lean application studies integrated into the job evaluation method has been proposed in a medium-sized manufacturing factory.